Developmental anatomy of the membranous part of the ventricular septum in the human heart. Issue 3 (March 1979) - Allwork, S P; Anderson, R H
Abstract : The anatomy of the membranous part of the ventricular septum is described in 25 hearts from patients ranging in age from 15 weeks of gestation to the ninth decade of adult life. Both atrioventricular and interventricular components were recognised in all the adult subjects, and the atrioventricular component was evident in all 25. The interventricular membranous septum was present in only 1 of the fetal hearts and 4 of the infant subjects. We consider that these findings indicate that the transformation of the membranous septum into atrioventricular and interventricular components occurs in the late fetal and early postnatal period rather than during closure of the embryonic interventricular foramen. It is associated with the liberation of the medial leaflet of the tricuspid valve from the muscular ventricular septum.